PENGARUH KOMUNIKASI PEMASARAN DAN EFISIENSI WAKTU TERHADAP MINAT PELANGGAN DALAM MENGGUNAKAN JASA PENGIRIMAN EKSPEDISI PADA PT. KEMASINDO CEPAT MEDAN - Ida Rosida Br Marbun; M. Amri Nasution; Asrindah Nasution (Jurnal Ilmu Sosial Dan Politik, 2022)
The purpose of this study was to determine the effect of marketing communications on customer interest in using expedited shipping services, to determine the effect of time efficiency on customer interest and to determine the effect of marketing communications and time efficiency on customer interest in using expedited shipping services at PT. Kemasindo Fast Medan. The data collection techniques used were documentation studies, observations and questionnaires, while the data analysis techniques used were multiple linear regression analysis, t test, F test and determination test. The partial results of testing the effect of marketing communications on customer interest show that tcount > ttable is 8.262 > 1.66256, which means that marketing communications have a significant effect on the variable of customer interest in using expeditionary shipping services at PT. Kemasindo Fast Medan. In addition, partial testing of the effect of time efficiency on customer interest shows that tcount > ttable is 13,957 > 1.66256, which means that time efficiency has a significant influence on customer interest in using expeditionary shipping services at PT. Kemasindo Fast Medan. Furthermore, the results of simultaneous testing of the effect of marketing communications and time efficiency on customer interest obtained the value of Fcount > Ftable, namely 131.262 > 3.10 or it can be concluded that marketing communications and time efficiency simultaneously affect customer interest in using expeditionary shipping services at PT. Kemasindo Fast Medan.